Sleep disorders and associated factors in children with cerebral palsy - Sari Wardhani Mahligai Patery; Sunartini Sunartini; Retno Sutomo (Paediatrica Indonesiana, 2021)
Background Sleep disorders are a condition affecting quality and quantity of sleep. Children with cerebral palsy (CP) have higher risk of sleep disorders than those with no chronic disease. Objective To determine the prevalence and factors associated with sleep disorders in children with CP. Methods We conducted an analytic, observational study with cross-sectional design in children aged 4-10 years with CP. Subjects were recruited consecutively; children with chronic diseases (cardiovascular, malignancy, chronic obstructive pulmonary disease, and diabetes mellitus) were excluded from the study. Primary data including sociodemographics, intensity of physiotherapy outside Sardjito General Hospital (SGH), sleep hygiene, and sleep disorders were collected from the Children’s Sleep Habit Questionnaire (CSHQ). Secondary data were acquired from medical records, such as type of CP, severity of motor function impairment, presence of epilepsy, intensity of physiotherapy performed at SGH, as well as anti-epileptic, anti-spastic, and sleep-affecting medicines. Results We found sleep disorders in 64 of 75 (85%) subjects, mostly bedtime resistance (66%). Spastic quadriplegia (OR=3.63; 95%CI 1.82 to15.94) and presence of epilepsy (OR=7.82; 95%CI 1.53 to 39.84) were significantly associated with sleep disorders in children with CP aged 4-10 years. Conclusion Sleep disorders are common in children with CP, with the majority experiencing bedtime resistance. Sleep disorders are more prevalent in subjects with spastic quadriplegia and epilepsy.